Czas w życiu osób w kryzysie bezdomności - Czapnik-Jurak, Marta (Kultura-Społeczeństwo-Edukacja, 2025)
The article addresses the issue of time in the context of individuals suffering from homelessness. It presents the results of the author’s research, carried out in Warsaw and its surrounding areas in the years 2016–2021. Methodologically, the research was carried out from a qualitative perspective and the research tool was an Individual In-Depth Interview (IDI). The research sample included 51 people – 36 men and 15 women. The aim of the research was to analyze how people living rough and people in accommodation for the homeless manage their time and whether – in this regard – there is a difference between “roofless” and “houselessness”. Important part of the research was to evaluate the impact of the organization of the homeless assistance system on the daily rhythm of its recipients. The study analyzed the temporal aspects of the assistance received, which includes distance of the support facilities and the time required to move between them, the opening hours of the facilities and the mechanisms for organizing time within them. The paper also addresses the issue of the temporal orientations of homeless people, raising questions which time framwork – past, presentist or future – dominates in analyzed group and how it affects participants in the long term.